2022
DOI: 10.3390/bios12110945
|View full text |Cite
|
Sign up to set email alerts
|

Alprazolam Detection Using an Electrochemical Nanobiosensor Based on AuNUs/Fe-Ni@rGO Nanocomposite

Abstract: Despite all the psychological advantages of alprazolam, its long list of toxic properties and interactions has caused concern and highlighted the need for a reliable sensing method. In this study, we developed a simple, highly sensitive electrochemical nanobiosensor to determine the desirable dose of alprazolam, averting the undesirable consequences of overdose. Gold nanourchins (AuNUs) and iron-nickel reduced graphene oxide (Fe-Ni@rGO) were immobilized on a glassy carbon electrode, which was treated beforehan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Nanomaterials that can be easily modied and functionalized are particularly important and preferred, among which, 2D nanomaterials have the unique advantage of being easily modied with other nanoparticles, such as precious metal nanomaterials 57,58 to form nanocomposites to achieve specic recognition and improve selectivity. For example, novel electrochemical biosensors for breast cancer based on carbon nanobers, 59 metal-organic skeletons, and magnetic graphene oxide nanocomposites can anchor larger targets using the large specic surface area of nanocomposites, since it could be modied with iron atoms to prevent single-chain shedding, achieve specic adsorption and improve selectivity. Au NPs signicantly improve selectivity due to the effect of specic covalent bond binding.…”
Section: Nanomaterials For Improving the Selectivity Of Electrochemic...mentioning
confidence: 99%
“…Nanomaterials that can be easily modied and functionalized are particularly important and preferred, among which, 2D nanomaterials have the unique advantage of being easily modied with other nanoparticles, such as precious metal nanomaterials 57,58 to form nanocomposites to achieve specic recognition and improve selectivity. For example, novel electrochemical biosensors for breast cancer based on carbon nanobers, 59 metal-organic skeletons, and magnetic graphene oxide nanocomposites can anchor larger targets using the large specic surface area of nanocomposites, since it could be modied with iron atoms to prevent single-chain shedding, achieve specic adsorption and improve selectivity. Au NPs signicantly improve selectivity due to the effect of specic covalent bond binding.…”
Section: Nanomaterials For Improving the Selectivity Of Electrochemic...mentioning
confidence: 99%
“…Despite their efficiency and specificity, they are unstable under harsh physicochemical conditions and are also expensive. With the advent of nanotechnology, several research fields benefited from the extraordinary properties of nanosized objects [ 1 , 2 , 3 , 4 , 5 , 6 ]. In 2007, it was accidentally found that magnetic nanoparticles mimic the function of horseradish peroxidase (HRP), albeit showing higher robustness [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modified electrode exhibited high sensitivity and applicability, with a lower limit of detection of 0.08 µmol L −1 in aqueous solution and 10 µmol L −1 in the contaminated ground chicken, and 100 µmol L −1 in the contaminated milk sample. Sadrabadi and co-workers [ 11 ] developed an electrochemical nanobiosensor to detect alprazolam, averting the undesirable consequences of overdose. GCE was immobilized with Gold nanourchins (AuNUs), and iron-nickel reduced graphene oxide (Fe-Ni@rGO).…”
mentioning
confidence: 99%